2013
DOI: 10.1039/c3sm50184a
|View full text |Cite
|
Sign up to set email alerts
|

Morphological transitions in polymer vesicles upon bilayer swelling with small hydrophobic molecules in water

Abstract: We show that when unilamellar polymer vesicles dispersed in water made from a blockcopolymer, in this case poly((ethylene oxide)45-block-(methyl methacrylate)164), poly((ethylene oxide)45-block-(methyl methacrylate)170), or poly(n-butyl methacrylate)81-block-(2-(dimethylamino)ethyl methacrylate)20, are exposed to small hydrophobic molecules, here methyl methacrylate as well as n-butyl methacrylate, they can undergo morphological transitions. Upon swelling, the polymersomes lose their original simple bilayer mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Generally, liposomes self-assembled from phospholipids and polymersomes self-assembled from amphiphilic block copolymers are conventional model vesicles. Similar to human red blood cells, vesicles have shown a rich variety of shapes or shape changes in both experimental and theoretical simulation studies. , For example, Michalet et al observed equilibrium shapes of topological genus-2 (shapes with two holes) liposomes, which were found to be in agreement with theoretical predictions on the basis of a minimization of the elastic curvature energy for fluid membranes . Markvoort et al studied the liposome deformations on osmotic deflation using coarse-grained molecular dynamics simulations, and prolate ellipsoid, pear-shaped, and budded vesicles were formed by changing the pH or ion concentration .…”
Section: Introductionmentioning
confidence: 92%
“…Generally, liposomes self-assembled from phospholipids and polymersomes self-assembled from amphiphilic block copolymers are conventional model vesicles. Similar to human red blood cells, vesicles have shown a rich variety of shapes or shape changes in both experimental and theoretical simulation studies. , For example, Michalet et al observed equilibrium shapes of topological genus-2 (shapes with two holes) liposomes, which were found to be in agreement with theoretical predictions on the basis of a minimization of the elastic curvature energy for fluid membranes . Markvoort et al studied the liposome deformations on osmotic deflation using coarse-grained molecular dynamics simulations, and prolate ellipsoid, pear-shaped, and budded vesicles were formed by changing the pH or ion concentration .…”
Section: Introductionmentioning
confidence: 92%